Establishing Correlates of Protection for Vaccine Development: Considerations for the Respiratory Syncytial Virus Vaccine Field - Kulkarni, Prasad S.; Hurwitz, Julia L.; Simões, Eric A.F.; Piedra, Pedro A. (Viral immunology, 2018)
Correlates of protection (CoPs) can play a significant role in vaccine development by assisting the selection of vaccine candidates for clinical trials, supporting clinical trial design and implementation, and simplifying tests of vaccine modifications. Because of this important role in vaccine development, it is essential that CoPs be defined by well-designed immunogenicity and efficacy studies, with attention paid to benefits and limitations. The respiratory syncytial virus (RSV) field is unique in that a great deal of information about the humoral response is available from basic research and clinical studies. Polyclonal and monoclonal antibodies have been used routinely in the clinic to protect vulnerable infants from infection, providing a wealth of information about correlations between neutralizing antibodies and disease prevention. Considerations for the establishment of future CoPs to support RSV vaccine development in different populations are therefore discussed.